2004
DOI: 10.1093/rheumatology/keh508
|View full text |Cite
|
Sign up to set email alerts
|

The influence of previous and concomitant leflunomide on the efficacy and safety of infliximab therapy in patients with rheumatoid arthritis; a longitudinal observational study

Abstract: The results indicate that the administration of infliximab after or simultaneously with leflunomide is safe and efficacious in RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 19 publications
3
14
0
2
Order By: Relevance
“…Two studies have found similar efficacy, whether measured using DAS28, American College of Rheumatology scores or treatment persistence, between anti-TNF in combination with either MTX or LEF 7 8. A further Dutch study (n=162), which compared anti-TNF persistence between those receiving LEF and those receiving any other DMARD(s), also found similar outcomes 28. In contrast Strangfeld et al 9 reported higher discontinuation rates of anti-TNF therapies (especially with INF) (n=1769) when combined with LEF than when combined with MTX, although this did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 89%
“…Two studies have found similar efficacy, whether measured using DAS28, American College of Rheumatology scores or treatment persistence, between anti-TNF in combination with either MTX or LEF 7 8. A further Dutch study (n=162), which compared anti-TNF persistence between those receiving LEF and those receiving any other DMARD(s), also found similar outcomes 28. In contrast Strangfeld et al 9 reported higher discontinuation rates of anti-TNF therapies (especially with INF) (n=1769) when combined with LEF than when combined with MTX, although this did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 89%
“…Leflunomide has been used in combination with biologicals, but the sample size of the studies are small, none were placebo controlled and different outcome measures were used [59][60][61][62][63].…”
Section: Clinical Efficacy N Rheumatology: Rheumatoid Arthritismentioning
confidence: 99%
“…Ком-бинация ЛФ и БП обеспечивала резкое повышение эффе-ктивности по сравнению с монотерапией. При этом пере-носимость лечения была примерно такой же, как и при использовании каждого препарата по отдельности [44][45][46][47]. В то же время одномоментное назначение ЛФ и БП сопровождалось повышением частоты нежелательных явлений [48].…”
Section: гу институт ревматологии рамн москваunclassified